SCIENTIFIC APPROACHES TO PEDAGOGICAL COMPETENCE IN DEVELOPED COUNTRIES - Rajabova Xurshida Xusanboyevna (Galaxy International Interdisciplinary Research Journal, 2023)
This research article investigates scientific approaches to pedagogical competence in developed countries, aiming to provide a comprehensive understanding of the methodologies employed in advanced educational systems. Through a mixed-methods research design comprising qualitative and quantitative analyses, the study explores competency frameworks, innovative pedagogies, professional development initiatives, and the integration of technology. Qualitative findings reveal the prevalence of established frameworks, a commitment to innovative teaching strategies, and a recognition of the importance of ongoing professional development. Quantitative results affirm positive perceptions of pedagogical competence among educators, with technology integration playing a significant role. The integration of qualitative and quantitative insights offers a nuanced perspective on pedagogical competence in developed countries, informing recommendations for educational practices, policy development, and future research endeavors.